Antibacterial and clusteroluminogenic hypromellose-graft-chitosan-based polyelectrolyte complex films with high functional flexibility for food packaging. (1st November 2021) - Lai, Wing-Fu; Zhao, Shuyang; Chiou, Jiachi
Abstract: Food packaging can extend the shelf life of food products and enhance the safety and quality of the food. This study reports food-grade polyelectrolyte complex films generated via electrostatic interactions between two cellulose-based agents [viz., hypromellose-graft-chitosan, and carmellose sodium]. At optimal conditions, our films show good barrier properties, high transparency, and high efficiency in post-production agent loading. They also demonstrate intrinsic antibacterial effects against both Gram-negative and Gram-positive bacteria. By using frozen chicken breasts as a model, the films enable real-time monitoring of the status of the frozen food due to the property of clusterisation-triggered emission. Along with their negligible toxicity, our films warrant further development as multi-functional films for effective and self-indicating food packaging. Graphical abstract: Unlabelled Image Highlights: Films are generated from hypromellose- graft -chitosan (HC) via polyelectrolyte complexation. The films show intrinsic antibacterial effects and clusterisation-triggered emission. Clusterisation-triggered emission of the films serves as an indicator of the status of the frozen food. Barrier properties of the films are affected by the mass percentage of HC. The films can be tailored by end users to meet the needs of various packaging applications.